AduLeT project: the community of practice platform - Gonçalves, Vitor (2018)
The innovation of Europe’s Higher Education systems results mainly from the use of emerging technologies for education and training. Higher education teachers should be prepared to have adequate knowledge, skills or abilities to deal with it in the most suitable way. Technology enhanced learning is the broad approach to using technology to support teaching and learning processes more effectively. In this sense, Advanced use of Learning Technologies in higher education (AduLeT) project has been set up, a collaborative research project funded by the European Commission, involving seven partner countries, running from November 2016 to August 2019. AduLeT aims to improve the teaching quality of lecturers by enhancing their skills regarding the use of technologies in an advanced way. It also aims at training the lecturer on how a specific teaching method can be combined with a certain technology in addition to providing guidelines, best practice and strategy concepts for lecturers and universities. This support system is being implemented as a community of practice (CoP) with all the results of the project and driven by pedagogical aspects. The CoP should also provide the possibility to get into contact with other lecturers and share experiences about teaching with Technology Enhanced Learning (TEL). The present paper intends to expose the system of CoP as well as its usage, explaining methods and tools, looking for a problem, user experiences and barriers. The platform consists in an application developed with an author programming tool which makes navigation and interaction flexible, visual, easy and coherent. The platform has been developed to provide users with a useful experience and to ensure inspired teaching and equipped with the skills required to enhance lectures’ current practice. Our experience shows that a CoP could facilitate the adaptation process and allow a faster and more effective transferability of teaching innovations between different countries as well as between lecturers and universities at a national level.